2017
DOI: 10.1038/s41598-017-15757-z
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of AGR2 expression in solid tumours: a systematic review and meta-analysis

Abstract: The prognostic value of anterior gradient-2 (AGR2) in tumours remains inconclusive. Here, we systematically reviewed the literature evidence and assessed the association between AGR2 expression and prognosis in solid tumours. The primary outcomes were overall survival (OS), disease-specific survival (DSS), and disease-free survival (DFS)/recurrence-free survival (RFS)/progression-free survival (PFS). All analyses were performed by STATA 12.0, with the hazard ratio (HR) or odds ratios (OR), and 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 49 publications
4
56
0
Order By: Relevance
“…This is important, as detection of these proteins in plasma/serum from the PDAC patients could be used to develop a simple blood-based test for determining NAC response in PDAC patients. Of note, TMED2, AGR2, and JTB are known to be associated with poor prognosis in other cancers (22)(23)(24) and thus, could be explored as novel biomarkers for predicting chemo-resistance in PDAC. Future studies, assessing the levels of these biomarkers in serum or plasma from the NAC-treated PDAC patients, will be required to confirm the clinical utility of these biomarkers as an indicator of chemo-resistance in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…This is important, as detection of these proteins in plasma/serum from the PDAC patients could be used to develop a simple blood-based test for determining NAC response in PDAC patients. Of note, TMED2, AGR2, and JTB are known to be associated with poor prognosis in other cancers (22)(23)(24) and thus, could be explored as novel biomarkers for predicting chemo-resistance in PDAC. Future studies, assessing the levels of these biomarkers in serum or plasma from the NAC-treated PDAC patients, will be required to confirm the clinical utility of these biomarkers as an indicator of chemo-resistance in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled odds ratio (OR) and 95% CI were used to analyze the associations between XIAP expressions and clinicopathological parameters. In our study, we utilized time to tumor progression (TTP) to represent four survival parameters (PFS, DFS, RFS, and time to biochemical progression; Tian et al, 2017 ≥6. Intensity of staining was scored as 0 (negative), 1 (weak), 2 (low), 3 (moderate), or 4 (strong).…”
Section: Discussionmentioning
confidence: 99%
“…Data extraction and quality assessmentNewcastle-Ottawa Scale (NOS;Wells et al, 2009) was used to assess the risk of bias(Mehrad-Majd et al, 2019;Tian et al, 2017), with emphasis on comparability, selection, and outcome assessment. We extracted the following data from eligible studies: surname of the first author, year of publication, cancer type, country, sample size, test method, age, follow-up time, cut-off values, and clinical outcomes.…”
mentioning
confidence: 99%
“…Its overexpression in numerous cancer types has been linked with enhanced cell migration and proliferation, altered adhesion and differentiation and promotion of angiogenesis and metastasis. 36 Previous studies have found elevated tissue expression of AGR2 to be an indicator of poor prognosis, 37 and it has been reported as a putative blood-borne biomarker for the detection and/or prognosis of ovarian, pancreatic, prostate and lung cancer. 25,[38][39][40] Our findings support AGR2 as a biomarker for early ovarian cancer detection that complements CA125 (and CHI3L1) when used longitudinally.…”
Section: Discussionmentioning
confidence: 99%